2016
DOI: 10.1021/acs.biochem.6b00323
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of a Bacterial Antifreeze Protein Indicates a Cooperative Effect between Its Two Ice-Binding Domains

Abstract: Antifreeze proteins make up a class of ice-binding proteins (IBPs) that are possessed and expressed by certain cold-adapted organisms to enhance their freezing tolerance. Here we report the biophysical and functional characterization of an IBP discovered in a bacterium recovered from a deep glacial ice core drilled at Vostok Station, Antarctica (IBPv). Our study showed that the recombinant protein rIBPv exhibited a thermal hysteresis of 2 °C at concentrations of >50 μM, effectively inhibited ice recrystallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 45 publications
4
22
1
Order By: Relevance
“…role of the cap subdomain in the overall stability of IBP [24] seem to be scaled down. This conclusion is further supported by the structure of the recently published two-domain protein IBPv [28], where each b-helix domain misses the cap subdomain but the protein has a Tm of 53.5°C [34], similar to that of capped IBP-1 fold proteins [23][24][25][26][27]. Overall, the low hydrophobicity of B and C faces might explain the only moderate TH activity of the protein.…”
Section: Activity Measurements Of Efcibp Mutantsmentioning
confidence: 68%
“…role of the cap subdomain in the overall stability of IBP [24] seem to be scaled down. This conclusion is further supported by the structure of the recently published two-domain protein IBPv [28], where each b-helix domain misses the cap subdomain but the protein has a Tm of 53.5°C [34], similar to that of capped IBP-1 fold proteins [23][24][25][26][27]. Overall, the low hydrophobicity of B and C faces might explain the only moderate TH activity of the protein.…”
Section: Activity Measurements Of Efcibp Mutantsmentioning
confidence: 68%
“…Other DUF3494‐containing proteins were also found in yeasts, algae, fungi and even archaea from regions that experience cold temperatures. In the last decade, increasing numbers of proteins containing the DUF3494 were demonstrated to bind ice crystals and, hence, were classified as IBPs . The current number of DUF3494 proteins confirmed as IBPs is so large that it raises the question of whether or not there are DUF3494s that do not bind to ice.…”
Section: The Duf3494 Protein Familymentioning
confidence: 99%
“…Currently, only two IBPs belonging to different DUF3494 architectures have been biochemically characterized. The first is IBPv, from the Flavobacteriaceae strain 3519–10 isolated from the Vostok lake . This protein contains two consecutive DUF3494 domains, connected by a 17‐residue linker and ending with a short C‐terminal domain (Fig.…”
Section: Architecture Of Duf3494 Ibpsmentioning
confidence: 99%
“…Third, functionalized AFPs should be engineered and developed to overcome the limitations of natural counterparts. Mother nature has suggested the use of RD3 and an IBP from Vostok glacial bacterium [137,209]. In both cases, connecting two almost homologous domains increases the TH value cooperatively compared with their monomeric AFPs [139,209].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Mother nature has suggested the use of RD3 and an IBP from Vostok glacial bacterium [137,209]. In both cases, connecting two almost homologous domains increases the TH value cooperatively compared with their monomeric AFPs [139,209]. Studies from the laboratories of Tsuda, Davies, and Holland have demonstrated that the multimerization of native type III AFP can increase TH activity [210,211,212].…”
Section: Conclusion and Perspectivementioning
confidence: 99%